From the manpower revolution to the activation paradigm. Explaining institutional continuity and change in an integrating Europe - Weishaupt, Timo J. (Amsterdam, 2011)
"This book examines the origins and evolution of labor market policy in Western Europe, while paying close attention to the OECD and the European Union as proliferators of new ideas. Three phases are identified: (a) a manpower revolution phase during the 1960s and 1970s, when most European governments emulated Swedish manpower policies and introduced/modernized their public employment services; (b) a phase of international disagreement about the root causes of, and remedies for, unemployment, triggering a diversity of policy responses during the late 1970s and 1980s; and (c) the emergence of an activation paradigm since the late 1990s, causing a process of institutional hybridization. The book's main contention is that the evolution of labor market policy is not only determined by historical trajectories or coalitional struggles, but also by policy makers' changing normative and cognitive beliefs. The cases studied include Austria, Denmark, Germany, Ireland, Sweden, and the United Kingdom. "